PERAN PPID DALAM MEWUJUDKAN KETERBUKAAN INFORMASI PUBLIK DI ACEH BARAT - Nurul Fahmi; Baihaqi (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This research discusses the role of Information and Documentation Management Officers (PPID) with the aim of looking at the extent to which the role of PPID in realizing public information disclosure in West Aceh. This study uses a qualitative approach with descriptive analytic method that is by describing the results of research from the findings in the field. Setap data obtained through two sources of primary data obtained directly in the field and secondary data, ie data directly collected by researchers as a supporter of the first source such as books, journals, print media, magazines, and other sources related to public information And information management officials. Based on the results of the research, the researcher sees that PPID has played a good role in realizing the public information disclosure by performing its tasks and functions so far, but there are also some other obstacles that can hinder the performance of PPID itself. Nevertheless, PPID continues to try to maximize the role it has mandated in implementing the pubic information openness, despite all the obstacles.